Economic well-being and poverty among the elderly: an analysis based on a collective consumption model - Laurens Cherchye; Bram de Rock; Frederic Vermeulen (Institute for the Study of Labor (IZA), 2008)
We apply the collective consumption model of Browning, Chiappori and Lewbel (2006) to analyse economic well-being and poverty among the elderly. The model focuses on individual preferences, a consumption technology that captures the economies of scale of living in a couple, and a sharing rule that governs the intra-household allocation of resources. The model is applied to a time series of Dutch consumption expenditure surveys. Our empirical results indicate substantial economies of scale and a wife's share that is increasing in total expenditures. We further calculated poverty rates by means of the collective consumption model. Collective poverty rates of widows and widowers turn out to be slightly lower than traditional ones based on a standard equivalence scale. Poverty among women (men) in elderly couples, however, seems to be heavily underestimated (overestimated) by the traditional approach. Finally, we analysed the impact of becoming a widow(er). Based on cross-sectional evidence, we find that the drop (increase) in material well-being following the husband's death is substantial for women in high (low) expenditure couples. For men, the picture is reversed.
Keywords: D11; 330; Collective model; intra-household allocation; indifference scales; economies of scale; poverty; Soziale Lage; Armut; Alte Menschen; Lebensstandard; Haushaltseinkommen; Skalenertrag; Zeitreihenanalyse; Schätzung; Niederlande